Employability of Persuasive and Rhetorical Strategies: A Corpus-Assisted Crititacal Discourse Analysis of Prime Minister Imran Khan’s Selected Address - Naeema Shah (University of Chitral Journal of Linguistics and Literature, 2020)
This study deals with the utilization of Persuasive and Rhetorical Strategies used by Prime Minister Imran Khan in his address to the nation on 17th March, 2020. This address was made in the background of Covid-19 pandemic. Aristotle’s concept of persuasive components namely ethos, pathos, and logos was followed to examine the utilization of these devices. Furthermore, rhetorical devices like rhetorical questions, inclusiveness and exclusiveness were also analyzed. Mixed Method approach was used to analyze the data. Quantitative data was obtained by using Corpus software Ant Conc, 3.5.8 (windows) 2019. Concordances were taken through this software, related to different devices and techniques. This numerical data was elaborated qualitatively. On the basis of the findings of the study, it can be said that PM Imran Khan practiced these techniques effectively and extensively.